Rapid state-dependent alteration in K(v)3 channel availability drives flexible synaptic signaling dependent on somatic subthreshold depolarization - Rowan, Matthew J.M. (Cell Rep, 2017)
In many neurons, subthreshold depolarization in the soma can transiently increase action potential (AP)-evoked neurotransmission via analog-to-digital facilitation. The mechanisms underlying this form of short-term synaptic plasticity are unclear, in part, due to the relative inaccessibility of the axon to direct physiological interrogation. Using voltage imaging and patch-clamp recording from presynaptic boutons of cerebellar stellate interneurons, we observed that depolarizing somatic potentials readily spread into the axon, resulting in AP broadening, increased spike-evoked Ca(2+) entry, and enhanced neurotransmission strength. K(v)3 channels, which drive AP repolarization, rapidly inactivated upon incorporation of K(v)3.4 subunits. This leads to fast susceptibility to depolarization-induced spike broadening and analog facilitation independent of Ca(2+)-dependent protein kinase C signaling. The spread of depolarization into the axon was attenuated by hyperpolarization-activated currents (I(h)) in the maturing cerebellum, precluding analog facilitation. These results suggest that analog-to-digital facilitation is tempered by development or experience in stellate cells.